Green intellectual capital and corporate economic sustainability: The mediating role of financial condition - Naveed Iqbal Chaudhry; Muhammad Amir Chaudhry (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2022)
This study aims to assess the effect of green intellectual capital on corporate economic sustainability in the manufacturing sector of Pakistan. Moreover, it also investigates whether the financial condition of a firm mediates the relationship between green intellectual capital and corporate economic sustainability. Data from the managers of 294 manufacturing firms were collected through a questionnaire and analyzed using SPSS and AMOS. Structural equational modeling has been used for hypotheses testing. Results indicate that green human capital and green relational capital significantly influence corporate economic sustainability while the effect of green structural capital is not significant. The results also elucidate that the financial conditions of a firm significantly mediate the impacts of green human capital, green structural capital, and green relational capital on corporate economic sustainability. Green intellectual capital facilitates the production of eco-friendly products and contributes to reducing waste, cost, time, and emission of harmful gases. Finally, study concludes that organizations should invest in green intellectual capital to meet the objective of corporate economic sustainability.
Keywords: 330; Green intellectual capital; green human capital; green structural capital; greenrelational capital; financial condition; corporate economic sustainability